How successfully is open-source research software adopted? Results and implications of surveying the users of a sensitivity analysis toolbox. (February 2020) - Pianosi, Francesca; Sarrazin, Fanny; Wagener, Thorsten
Abstract: Open-source research software is an important element of open science. While the number of software packages made available by researchers is increasing, there has been little analysis about their subsequent uptake. We collect basic information about prospective users when sharing our open-source sensitivity analysis toolbox. This enabled us to carry out a user survey to assess adoption success – beyond simply counting download numbers. Survey results confirm the key role of extensive documentation to ensure adoption, to enhance learning and to enable research implementation. We found that workflows are an effective tool to guide users to tailor methods to their problems. However, workflows also need to include guidance for interpretation of results, otherwise sophisticated functionalities are overlooked as their value is unclear. Developing effective documentation requires significant time investment but is essential if the ultimate aim of open research software is to promote the adoption of scientific methodologies and best practices. Highlights: Sharing open software has become common among researchers but is rarely followed up by an analysis of its uptake. We surveyed our toolbox users and found that workflows effectively enable uptake and tailoring of methods. We also realized that effective uptake requires not only guidance to produce results but also to their interpretation.